Oxygen metabolism in human placenta mitochondria (2014)
Due to the high metabolic demands of the placental tissue during gestation, we decide to analyzed the mitochondrial bioenergetic functions in the human term placenta. Different mitochondrial morphological parameters, membrane potential and cardiolipin content were determined by flow cytometry. Oxygen uptake, hydrogen peroxide production and cytochrome P450 content, were also measured. Some apoptotic mitochondrial proteins were also analyzed by western blot. Two isolated mitochondrial fractions were observed: large/heavy and small/light with different functional characteristics. Oxygen uptake showed a respiratory control (RC) of 3.4?±?0.3 for the heavy mitochondria, and 1.1?±?0.4 for light mitochondria, indicating a respiratory dysfunction in the light fraction. Good levels of polarization were detected in the heavy fraction, meanwhile the light population showed a collapsed ??m. Increased levels of cytochrome P450, higher levels of hydrogen peroxide, and low cardiolipin content were described for the light fraction. Three pro-apoptotic proteins p53, Bax, and cytochrome c were found increased in the heavy mitochondrial fraction; and deficient in the light fraction. The heavy mitochondrial fraction showed an improved respiratory function. This mitochondrial fraction, being probably from cytotrophoblast cells showed higher content of proteins able to induce apoptosis, indicating that these cells can effectively execute an apoptotic program in the presence of a death stimulus. Meanwhile the light and small organelles probably from syncytiotrophoblast, with a low oxygen metabolism, low level of ??m, and increased hydrogen peroxide production, may not actively perform an apoptotic process due to their deficient energetic level. This study contributes to the characterization of functional parameters of human placenta mitochondria in order to understand the oxygen metabolism during the physiological process of gestation.